Landfill leachate treatment by a boron-doped diamond-based photo-electro-Fenton system integrated with biological oxidation: A toxicity, genotoxicity and by products assessment. (15th June 2020) - Pellenz, Leandro; Borba, Fernando Henrique; Daroit, Daniel Joner; Lassen, Manoel Francisco Mendes; Baroni, Suzymeire; Zorzo, Camila Fernanda; Guimarães, Raíssa Engroff; Espinoza-Quiñones, Fernando Rodolfo; Seibert, Daiana
Abstract: A photo-electro-Fenton (PEF) reactor employing boron-doped diamond (BDD) and soft iron anodes was studied in landfill leachate (LL) treatment. The reactor operation parameters (ROP) H2 O2 concentration, current intensity and flow rate were investigated in the removal of Abs 254 nm. The PEF process with BDD anode, operating at the best operational conditions, was used as a pre-treatment and enabled biological oxidation (BO). The treatment strategy of PEF followed by BO showed to be the most efficient, reaching reductions of 77.9% chemical oxygen demand (COD), 71.5% total carbon (TC) and 76.3% radiation absorbance in 254 nm (Abs 254 nm), as well as a significant reduction in the genotoxicity ( Allium cepa ), observed by an increase in the mitotic index (MI) (131.5%) and decrease in the abnormalities (47.8%). The reduction of the toxic potential of LL using the integration of processes was also observed in the gas chromatography-mass spectrometry (GC-MS) byproducts analysis, which indicated the removal of emerging contaminants, such as Bisphenol-A (BPA), N, N-Diethyl-3-methylbenzamide (DEET) and Diisooctyl phthalate (DIOP). Thus, the PEF process integrated with BO presented a considerable efficiency in the removal of contaminants present in LL, becoming an alternative for the minimization of the environmental impacts caused by the discharge of this effluent in the environment. Graphical abstract: Image 1 Highlights: A new configuration of a PEF reactor was proposed and studied. BDD and soft iron anodes were compared. Intermediary byproducts were identified in (un) treated LL. PEF was integrated with BO. Reduction of phytotoxicity, genotoxicity and LL purification.